Thematic Interior at the Indischetafel Café As a Media for Forming Bandung Tempo Dulu’s Athmosphere - Tiara Isfiaty; Tri Widianti Natalia (LP2M ISBI Bandung, 2017)
Abstract The interior elements designed in a specific theme are aimed to shape the character, perception and space atmosphere. In Bandung, culinary facilities that carry the theme of the old-style interior design of Dutch East Indies are quite popular. This study aims to contribute guidance in creating the quality of space by applying the selection of decoration and furniture elements (moveableinterior elements) and the arrangement of walls, floors and ceilings (unmoveableinterior elements).This study applies case study research methods, discussion analysis uses descriptive analysis method and direct observation to Indischetafel café. The result of this study is to examine aspects of interior element arrangement in the Indischetafel café in bringing the atmosphere of Bandung Tempo Dulu.Keywords: thematic interior, interior elements, Bandung space atmosphere First Tempo